Implementasi Manajemen Pemasaran Pendidikan dengan Pendekatan Storytelling untuk Meningkatkan Citra Madrasah - Yusuf Khunaifi, A’an; Izzah, Khoirotul; Nurjana, Siti (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Marketing management is a plan carried out for school promotion. carried out by each institution for promotional events. Therefore, educational institutions must improve the general public's perception of the institution. To ensure that schools are of a high caliber, appropriate educational marketing strategies must be used. One component of school marketing strategies in the education sector is how the general public can obtain important school information. The reputation of the school can be improved through efficient public information transmission.  MTs Negeri 6 Kediri educational marketing model, the method used to implement educational marketing strategies factors that help and hinder the use of educational marketing at MTs Negeri 6 Kediri are the three main objectives of this study. Storytelling has evolved into a very helpful technique in the field of education that enables pupils to explore their understanding and creativity. Narrative in education is a strategy that blends storytelling with active learning, not merely retelling stories. By fusing narrative components with instructional content, teachers may give students rich and lasting learning experiences. Students' cognitive and emotional engagement with this approach improves their comprehension of the concepts being taught.